2013
DOI: 10.1021/jo401210r
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cascade Synthesis of Poly-Heterocyclic Architectures from Indigo

Abstract: The base-induced propargylation of the dye indigo results in the rapid and unprecedented one-pot synthesis of highly functionalized representatives of the pyrazino[1,2-a:4,3-a′]diindole, pyrido[1,2-a:3,4-b′]diindole and benzo [b]indolo [1,2-h]naphthyridine heterocyclic systems, with the last two reflecting the core skeleton of the anticancer/antiplasmodial marine natural products fascaplysin and homofascaplysins and a ring Bhomologue, respectively. The polycyclic compounds 6-8, whose structures were confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…This initial reaction indicated that indirubin is significantly less reactive than the corresponding indigo. The use of substituted allyl bromides continued the trend with the pink mono allylated derivatives (Type B) being produced in yields from 20-49% in 16 hour reactions (entries [1][2][3][4], with an extended 20 hour reaction required to produce the N'-cinnamylindirubin 13 (21%).…”
Section: Synthesis and Product Identificationmentioning
confidence: 79%
See 1 more Smart Citation
“…This initial reaction indicated that indirubin is significantly less reactive than the corresponding indigo. The use of substituted allyl bromides continued the trend with the pink mono allylated derivatives (Type B) being produced in yields from 20-49% in 16 hour reactions (entries [1][2][3][4], with an extended 20 hour reaction required to produce the N'-cinnamylindirubin 13 (21%).…”
Section: Synthesis and Product Identificationmentioning
confidence: 79%
“…This surprising result revealed a new arena in the previously unreported chemistry of indigo, allowing access to unique, relatively complex heterocycles in one pot. [1][2][3] The structural isomers of indigo 1, indirubin 2 and isoindigo 3 ( Figure 2), are known, 4 but knowledge of their chemistry is still limited. Indirubin is the most well studied due to the reported biological activity of derivatives, known to suppress the metastatic ability of human head and neck cancer cells 5 and to reduce the invasion of glioma cells both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, S. Yamabe showed that the related benzilic type rearrangement of a-diketones involving a carbanion [1,2] migration 55 included both alkyl and aryl groups as migrating units. Surprisingly, in alkaline conditions, we managed to obtain the target g-carbolines and to avoid the formation of the rearrangement byproducts 4, 5 as the major products.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] Our research in the eld of cascade reactions began with the discovery of a cationic domino reaction of hemiindigos that afford pentacyclic 3-hydroxyindolenines related to indolenine alkaloids in a diastereoselective fashion under the NMR experiment conditions. 32 This is the rst example of the acid-catalyzed domino reaction that involved homocoupling of hemiindigos 1 followed by a reverse Wagner-Meerwein [1,2] type rearrangement of the intermediate 2-spiropseudoindoxyls. 32 We also described novel cationic domino reactions of hemiindigos 1 in the absence or in the presence of an external nucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…The design and synthesis of desired and tolerable methods to attain complex molecules from appropriate starting materials are still challenging work for lots of scientific areas such as modern synthetic and medicinal chemistry. The methods which include synthesis of compounds containing nitrogen and oxygen are of growing importance due to the importance of some biological activities [1a-c]. Some important heterocyclic compounds such as antituberculosis agent 1 (PA‐824), antibiotic, sold under the trade name Levaquin 2 , and acortatarin A 3 which is an inhibitor for the production of reactive oxygen species (ROS) include oxazine cores (Figure ).…”
Section: Introductionmentioning
confidence: 99%